Pengaruh Temperatur Pada Microwave Pirolisis Cangkang Kelapa Sawit dan Low Density Polyethylene Dengan Katalis Zeolite/Kalsium Oksida - Ayatullah, Maulana Wahyu; Saptoadi, Harwin (Proceedings Series on Physical & Formal Sciences, 2021)
In general, the use of oil palm parts can be utilized by industry, but it is different from oil palm shells which become waste. The high use of plastic is proportional to the waste generated. So far, both types of waste are problems that have not been resolved. The utilization of waste shell waste and low-density polyethylene using the pyrolysis method. Microwave technology has been widely used as a heat source in the pyrolysis process. The advantages of using microwaves in pyrolysis are fast and selective heating, efficient energy use, and control of pyrolysis products. This study aimed to determine the characteristics of Pyrolytic-oil from the pyrolysis of waste oil palm shells and Low-density polyethylene. The research was conducted using a microwave with temperature variations of 400oC, 450oC, 500oC, 550oC and 600oC. The composition of the main ingredients consisted of 75 grams of palm shells, 75 grams of low-density polyethylene plastic, 56.25 grams of a zeolite catalyst, 56.25 grams of calcium oxide and 131.25 grams of charcoal carbon absorber. The results showed the effect of temperature on pyrolytic-oil productivity; as the temperature increases, the product gas increases. The lowest density value at a temperature of 400oC is 966.8 Kg/m. The lowest viscosity at a temperature variation of 500oC is 2.1 Mpa.s. The highest acidity value is at a temperature of 550oC.